Performance evaluation of the dairy farmers regarding adoption of precise dairy farming practices in the Punjab, Pakistan (African Journal of Dairy Farming and Milk Production, 2013)
Livestock is the dominant cog of economy of Pakistan and also livelihood supporter fulfiller for the subsistent farmers of country. The country has a great potential and prosperous with dairy animals’ breeds. Unfortunately, farmers are so far away to cash in the actual potential of animals. Non-adoption of improved practices is the major productivity retarding factor. In this regard, present study was conducted in the different areas of Punjab, Pakistan. Data were collected from the 107 livestock farmers. The sample was a blend of landless, illiterate and young, middle aged and small farmers who were immensely dependent on livestock. Data analysis indicated that cattle were the more likely animal among farmers. Farmers were interested in different management practices regarding feeding, breeding and disease management. However, farmers were adopting the only practice which needs no investment and technicality. Farmers were lacking in technical knowledge=2.81) were other constraints compelling farmers to adopt traditional practices. Correlation analysis indicated highly significant association of age, education, land size and annual income with adoption of scientific dairy practices. On the basis of results, it is suggested that the role of livestock extension should be diversified under strict evaluation. Micro credit schemes with cooperation of government may also boost the adoption. It is also inferred that international organization may also start some projects keeping in mind the ultimate potential of Pakistan dairy sector.